Effects of surface tension on the suction forces generated by miniature craters. (September 2017) - Wang, Liu; Qiao, Shutao; Lu, Nanshu
Abstract: There are emerging demonstrations that micro- or nano-craters engineered on polymer surfaces can enable enhanced adhesion. In the past, we have developed a framework for quantifying the suction forces produced by isolated macroscopic craters neglecting surface effects. In this paper, we take surface tension into consideration because it plays a significant role in miniature craters on soft polymers. We have derived linear and nonlinear elastic solutions for the elasto-capillary distortion in miniature hemi-spherical craters when they are demolded from the template. By implementing a user-element subroutine in finite element modeling (FEM) software ABAQUS, we have also simulated the demolding, compression, and unloading processes of the craters subjected to surface tension under large deformation. With the simulated volume changes of the crater, pressure drop and suction force can be deduced. We find that surface tension induced crater contraction has a negative effect on the generation of suction forces. We discover that reinforcing the crater surface by a thin and stiff shell can help sustain the crater shape after demolding. The effects of shell thickness and stiffness are quantitatively investigated through FEM and optimal parametric combinations are identified.